Single‐Dose Pharmacokinetics, Safety, and Tolerability of Avadomide (CC‐122) in Subjects With Mild, Moderate, or Severe Renal Impairment. Issue 7 (31st December 2019) - Li, Yan; MacGorman, Kimberly; Liu, Liangang; Chen, Jian; Hoffmann, Matthew; Palmisano, Maria; Zhou, Simon
Abstract: CC‐122 (Avadomide) is a nonphthalimide analogue of thalidomide that has multiple pharmacological activities including immune modulation of several immune cell subsets, antigrowth activity, antiproliferative activity, and antiangiogenic activity. CC‐122 as monotherapy and in combination with other agents is being evaluated for multiple indications including hematologic malignancies and advanced solid tumors. Given that renal clearance is one of the major routes of elimination for CC‐122 and its clearance/exposure could be affected by renal impairment, a total of 50 subjects with various degrees of renal function were enrolled in an open‐label, single‐dose study to evaluate the impact of renal impairment on CC‐122 pharmacokinetic disposition. The study showed that following administration of a single oral dose of 3 mg CC‐122, renal impairment reduced both the apparent total plasma clearance and renal clearance of CC‐122, but it had less impact on CC‐122 absorption, as demonstrated by similar Tmax and Cmax among groups with various degrees of renal function. Compared with exposure in subjects with normal renal function, total plasma exposure to CC‐122 increased by ∼20%, ∼50%, and ∼120% in subjects with mild, moderate, and severe renal insufficiency, respectively. Results from this study combined with modeling/simulation suggest that dose adjustments are necessary in patients with moderate or severe but not with mild renal impairment. Finally, a single dose of 3 mg CC‐122 was safe and well tolerated by healthy subjects and subjects with mild, moderate, and severe renal impairment.